Virtual internship programme: A curriculum innovation - Khairudin, Norhaiza; Abdul Hamid, Mohd Noor; Ibrahim, Marhaiza; Salleh, Danilah (2022)
Virtual internship programme allows students to obtain real-world work experience in a business environment anytime, anyplace, and at any pace. Participants in virtual internship programmes have the flexibility of working from home or school using personal or campus computing facilities. As long as the student has a phone, Internet and fax, he/she can work from virtually anywhere. Instructors can meet with their interns online to provide guidance and feedback. Most significantly, virtual internships eliminate geographical barriers and let students gain expertise and learning from instructors and business professionals from anywhere. Many businesses today are accepting students doing virtual internship programmes at their firms. Nevertheless, it is found that less research has been done to study these issues, proving that there is a knowledge gap issue in this area of study. This paper therefore presents the emerging opportunity and need for virtual internship program in future, based on the digital working era, where there is a crucial need to revise and redesign the assessment rubric which can be used to assess virtual internship programmes.